Kelas Pangan Berbasis Lokal sebagai Upaya Penurunan Stunting Balita: Pengabdian - Eva Oktaviani; Rehana; Jawiah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Stunting is one of the chronic nutritional problems that is still a major challenge in Indonesia, especially for toddlers. The main factor causing stunting is inadequate nutritional intake in the long term, especially in the first 1000 days of life. Efforts to overcome stunting require a holistic approach and are based on local wisdom, through the implementation of local-based food classes. This community service activity aims to improve the knowledge and skills of the Pegayut village community in utilizing nutritious, easily accessible, and culturally appropriate local food as an effort to deal with stunting. The implementation method involves nutrition education, demonstrations of local food processing. The results of this activity show an increase in participants' understanding of stunting prevention through local food classes and active participation during cooking classes. Local-based food classes are a sustainable nutrition strategy that is adaptive and worthy of being replicated according to local wisdom